2021
DOI: 10.3390/foods10030612
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Insights in Sensory Profile of Sweet Cherries

Abstract: Sweet cherry (Prunus avium L.) is a fruit appreciated by consumers for its well-known physical and sensory characteristics and its health benefits. Being an extremely perishable fruit, it is important to know the unique attributes of the cultivars to develop cultivation or postharvest strategies that can enhance their quality. This study aimed to understand the influence of physicochemical characteristics of two sweet cherry cultivars, Burlat and Van, on the food quality perception. Several parameters (weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 60 publications
0
20
0
3
Order By: Relevance
“…Low DMC in fruit can cause customer dissatisfaction [42] and reduce rates of repurchase [43]. Therefore, given the correlation found between TSS and DMC in this study, we suggest that consumer preference for high TSS cherries [44] may be contributed to by DMC. The results in Table 7 suggest, but do not prove, that training systems have significantly more influence on fruit quality than can be summarised by the respective system effects on light interception.…”
Section: Light Interception and Fruit Qualitymentioning
confidence: 59%
“…Low DMC in fruit can cause customer dissatisfaction [42] and reduce rates of repurchase [43]. Therefore, given the correlation found between TSS and DMC in this study, we suggest that consumer preference for high TSS cherries [44] may be contributed to by DMC. The results in Table 7 suggest, but do not prove, that training systems have significantly more influence on fruit quality than can be summarised by the respective system effects on light interception.…”
Section: Light Interception and Fruit Qualitymentioning
confidence: 59%
“…Table 2 shows several characteristics of the fruit by physical and chemical analysis. From the statistical analysis it is observed that the cultivars 'Regina' and 'New Star' show significant The dry matter content is very important for sweet cherries, because consumers appreciate it for its sensory characteristics and health benefits (Silvia et. al, 2021).…”
Section: Table 1 the Main Fructification Phenophases Of Studied Sweet...mentioning
confidence: 99%
“…Сьогодні зростає інтерес до біологічно активних сполук у кісточкових плодів. Це призводить до необхідності підбору не лише культур, але і окремих сортів із більш високим умістом вітамінівантиоксидантів [2,16,22]. Плоди черешні -джерело багатьох поживних і біологічно активних речовин, що необхідні для здоров'я людини.…”
Section: вступunclassified
“…Плоди черешні -джерело багатьох поживних і біологічно активних речовин, що необхідні для здоров'я людини. Вміст у плодах черешні кількості вітаміну С дає змогу розглядати їх як компоненти функціональної їжі в харчуванні людини [22]. Завдяки наявності у плодах біологічно активних поживних речовин у вигляді фітонутрієнтів і антиоксидантів спостерігаємо властивість фруктів виявляти профілактичну дію проти розвитку серцево-судинних захворювань, діабету і раку, що пов'язано з окислювальним стресом [7,19].…”
Section: вступunclassified